2016
DOI: 10.1093/jac/dkw146
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of an HIV DNA resistance genotypic test in patients who are candidates for a switch to the rilpivirine/emtricitabine/tenofovir disoproxil fumarate combination

Abstract: Incomplete information provided by the DNA genotypic test is more notable in patients with VF, suggesting that all resistance mutations associated with prior VF have not been archived in the proviral DNA or decreased to a level below the threshold of detection. In the case where no historical plasma genotypic test is available, DNA testing might be useful to rule out switching to rilpivirine/emtricitabine/tenofovir disoproxil fumarate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Outside the guidelines, in the absence of prior plasma genotype data, it has been suggested that a proviral DNA genotype in peripheral blood mononuclear cells (PBMCs) in the virologically suppressed patient might provide information on archived mutations .…”
Section: Considering the Evidence For Switch – What The Guidelines Saymentioning
confidence: 99%
“…Outside the guidelines, in the absence of prior plasma genotype data, it has been suggested that a proviral DNA genotype in peripheral blood mononuclear cells (PBMCs) in the virologically suppressed patient might provide information on archived mutations .…”
Section: Considering the Evidence For Switch – What The Guidelines Saymentioning
confidence: 99%
“… 17 Other studies showed that switch regimens, as bictegravir/emtricitabine/tenofovir alafenamide and abacavir/lamivudine/dolutegravir triple therapy and ART-PRO for dual therapy, were successful in the absence of historical M184V in baseline PBMCs. 18 , 19 The choice of ART in the clinic has always been based on the study of genotype mutations by Sanger sequencing. Some studies have showed that choosing treatment based on ultradeep mutations has a limited impact on virological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Lambert-Niclot et al found good concordance between DNA and RNA GRT only in absence of prior virological failure. 11 DNA GRT could be useful in a virologically suppressed patient in the absence of prior RNA GRT, or in case of history of virological failure while receiving NNRTI and no RNA GRT at the time of failure. Use of rilpivirine should be avoided if resistance-associated mutations are detected using a DNA GRT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest an interest of proviral DNA GRT before switching therapy in patients successfully suppressed when no historical RNA resistance test is available. 11,12 In France, November 2016 and May 2017 updates of national guidelines proposed to realize proviral DNA GRT in PBMC in patients with virological failure with low-level viremia and unsuccessful RNA resistance test and in patients successfully suppressed when no historical RNA resistance test is available and a switch of therapy is planned. 2 However, several issues have been raised concerning HIV proviral DNA GRT.…”
Section: Introductionmentioning
confidence: 99%